Melastomataceae in the Parque Estadual da Serra Dourada, Goiás state, Brazil - Machado, Ana Isa Marquez Rocha; Romero, Rosana (Phytotaxa, 2020)
Melastomataceae is represented in the Parque Estadual da Serra Dourada by 42 taxa in 14 genera. Miconia is the most representative genus, with 18 species, followed by Tibouchina, with five, Microlicia and Pleroma with four species each, and Clidemia with two species. Acisanthera, Cambessedesia, Desmoscelis, Macairea, Pterolepis, Rhynchanthera, Siphanthera, Tococa, and Trembleya have one species each. This study provides a key to the species, descriptions, comments about morphological characters, geographical data, and the flowering and fruiting periods of each species, as well as illustrations of the species that are poorly illustrated in the literature.